2011
DOI: 10.1093/rheumatology/ker090
|View full text |Cite
|
Sign up to set email alerts
|

Autopathogenic correlation of periodontitis and rheumatoid arthritis

Abstract: Recently, a number of studies have pointed to a potential relationship between periodontitis (PO) and RA and vice versa. Both diseases are characterized by chronic inflammation, osseous destruction, damage of the supporting soft tissues, similar cellular immune responses and common immunogenetic findings. Although a definite, methodological report associating these diseases is missing from the literature, it is possible that both diseases share a common aetiopathogenic background. This background includes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 35 publications
0
40
0
1
Order By: Relevance
“…Rheumatoid arthritis and periodontal disease share a number of pathobiologic processes that have been previously reviewed [21,38 ■■ ,39,40 ■ ,41–43, 44 ■ ]. These include similar cellular participation at the inflammatory focus, microenvironmental and serum cytokine, matrix metalloproteinase and other mediator profiles, and osteoclast-mediated bone destruction.…”
Section: Moving From Clinical Associations To Mechanismmentioning
confidence: 99%
“…Rheumatoid arthritis and periodontal disease share a number of pathobiologic processes that have been previously reviewed [21,38 ■■ ,39,40 ■ ,41–43, 44 ■ ]. These include similar cellular participation at the inflammatory focus, microenvironmental and serum cytokine, matrix metalloproteinase and other mediator profiles, and osteoclast-mediated bone destruction.…”
Section: Moving From Clinical Associations To Mechanismmentioning
confidence: 99%
“…Periodontitis is caused by chronic bacterial infections of the gingiva with subsequent destruction of the periodontal attachment and alveolar bone 19. The relationship between RA and periodontitis is supported by pathological and immunological data 20 21 . Porphyromonas gingivalis (P gingivalis) , a major pathogenic bacterium of periodontitis, is the sole micro-organism known to express peptidyl arginine deiminase,22 which leads to citrullination, an irreversible, post-translational conversion of arginine to citrulline 15 23.…”
Section: Introductionmentioning
confidence: 97%
“…In addition to being a major cause of tooth loss, periodontal disease has also been associated with several systemic diseases. Animal-and population-based studies have demonstrated associations between periodontal disease and diabetes, cardiovascular disease, rheumatoid arthritis, stroke, and adverse pregnancy outcomes (4,8,38). Although the mechanisms that cause these associations are far from being completely understood, more reliable detection of early stage periodontal disease could have widespread health benefits, even beyond the prevention of tooth loss.…”
mentioning
confidence: 99%